Enhancement Heat Transfer in a double pipe Heat Exchanger through Varied Fin Geometries under Turbulent Flow Conditions - BECER Abdesselam; Zaid Bouaziz; Touati Tlaib Abdelfettah; Youcef Ladjali (University of Shahid Hama Lakhdar - El Oued, 2024)
Double-pipe heat exchangers have gained significant economic importance. It is estimated that nearly all of the generated thermal energy passes through a heat exchanger at least once. The thermal-hydraulic properties of a double-pipe heat exchanger were analyzed with the aim of improving its performance. Three main pipe configurations were studied: smooth cylindrical, smooth triangular, and smooth trapezoidal with varied convex arrangements. Hot and cold water were the fluids used in this study. The governing equations were solved using the finite volume method based on the SIMPLE algorithm for pressure-velocity coupling. The standard model was used to describe the turbulence phenomenon. Simulations were performed using the "ANSYS FLUENT" code. The results indicated that the type of pipe and the arrangement of the corrugations significantly affect the thermalhydraulic performance of the heat exchanger. اكتسبت المبادالت الحرارية ذات األنابيب المزدوجة أهمية اقتصادية كبيرة. تشير التقديرات إلى أن جميع الطاقة الحرارية المولدة تقريبًا تمر عبر مبادل حراري مرة واحدة على األقل. تم تحليل الخصائص الحرارية الهيدروليكية لمبادل حراري مزدوج األنبوب بهدف تحسين أدائه. تم دراسة ثالث تشكيالت لألنابيب الرئيسية: أسطوانية ملساء، مثلثية ملساء، وشبه منحرفه ملساء ذات ترتيبات محدبة ومتنوعة. وكانت المياه الساخنة والباردة هي السوائل المستخدمة في هذه الدراسة. تم حل المعادالت الحاكمة باستخدام طريقة الحجم المحدود المعتمدة على خوارزمية اقتران السرعة والضغط البسيطة. تم استخدام النموذج القياسي لوصف ظاهرة االضطراب. تم إجراء عمليات المحاكاة باستخدام كود " FLUENT ANSYS". أشارت النتائج إلى أن نوع األنبوب وترتيب التموج يؤثران بشكل كبير على األداء الحراري الهيدروليكي للمبادل الحراري.
Master's thesis specializing in energy
Keywords: corrugated; heat transfer; heat exchanger; double pipe; turbulent flow; المموجة: نقل الحرارة، المبادل الحراري، أنبوب مزدوج، التدفق المضطرب